2021
DOI: 10.1016/j.psj.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The application of reduced dietary crude protein levels supplemented with additional amino acids in laying ducks

Abstract: This study was aimed at studying use of reduced dietary crude protein ( CP ) level supplemented with additional amino acids in laying ducks. A total of 720 Jingjiang ducks (50 wk) were randomly assigned to 5 treatments and fed 5 basal diets with CP levels at 17.5, 16.5, 15.5, 14.5, or 13.5%, with additional amino acids added to each diet for 12 wk. Each treatment had 6 replicates of 24 ducks each. Dietary CP levels affected ( P < 0.05) egg production and mass of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Thirty eggs in the second breeding cycle of lactation were randomly selected from each treatment group according to several similar studies ( Zhang et al., 2021 ; Jin et al., 2022 ). Before measuring, all the eggs were stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty eggs in the second breeding cycle of lactation were randomly selected from each treatment group according to several similar studies ( Zhang et al., 2021 ; Jin et al., 2022 ). Before measuring, all the eggs were stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In support of this, serum ALT, AST, triglycerides, cholesterol, LDL, VLDL, total bilirubin, and direct and indirect bilirubin contents remained unchanged in response to increasing dietary Lys. Blood albumin and total protein concentrations are trustworthy indicators of hepatic function and, collectively with blood AST and ALT levels and blood lipid profile, are closely related to the extent of hepatic lipidosis [ 53 , 54 ]. Excessive dietary L-lysine·H 2 SO 4 was reported to diminish the hepatic physiological function, causing the deposition of lipoprotein in the liver and liver damage [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serum AST activity was elevated with decreasing CP levels and this elevation was associated with the disorganization of hepatocytes, moderate degeneration of hepatic cells, vacuolated hepatic cells, excessive connective tissue, and lymphocytic infiltration. Our results indicated that the liver function status might be, to some extent, disrupted by decreasing the dietary CP content [ 53 ]. Consistent with our findings, Zhang et al [ 53 ] reported an increase in serum ALT and AST activities with decreasing CP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of the Internet of Things and environmental monitoring has become a new development trend in environmental monitoring and management [3]. Some people have applied the Internet of things technology to agricultural greenhouse environmental monitoring and pest monitoring.…”
Section: Introductionmentioning
confidence: 99%